A Polyoxometalate‐Encapsulating Cationic Metal–Organic Framework as a Heterogeneous Catalyst for Desulfurization. Issue 9 (21st January 2015) - Hao, Xiu‐Li; Ma, Yuan‐Yuan; Zang, Hong‐Ying; Wang, Yong‐Hui; Li, Yang‐Guang; Wang, En‐Bo
Abstract A new cationic triazole‐based metal–organic framework encapsulating Keggin‐type polyoxometalates, with the molecular formula [Co(BBPTZ)3][HPMo12O40]⋅24 H2O [compound 1; BBPTZ=4, 4′‐bis(1, 2, 4‐triazol‐1‐ylmethyl)biphenyl] is hydrothermally synthesized and characterized by elemental analysis, IR spectroscopy, thermogravimetric analysis, powder X‐ray diffraction, and single‐crystal X‐ray diffraction. The structure of compound 1 contains a non‐interpenetrated 3D CdSO4 (cds)‐type framework with two types of channels that are interconnected with each other; straight channels that are occupied by the Keggin‐type POM anions, and wavelike channels that contain lattice water molecules. The catalytic activity of compound 1 in the oxidative desulfurization reaction indicates that it is not only an effective and size‐selective heterogeneous catalyst, but it also exhibits distinct structural stability in the catalytic reaction system.